Tanggung Jawab Pemerintah Daerah Dalam Menyediakan Aksesibilitas Bagi Penyandang Disabilitas Pada Fasilitas Publik - Louhenapessy, Revally; Sedubun, Victor Juzuf; Pattinasarany, Yohanes (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Disability is often defined as an illness or injury that impairs and limits a person's mental and physical abilities or the state of being unable to do things in an unusual way.Methods of the Research: The research method used is normative juridical research, the type of research is analytical descriptive. The sources of legal materials used are primary, secondary and tertiary legal materials. The legal material collection technique used in this research is through library research. Analysis of legal materials is descriptive qualitative.Results of the Research: Based on the analysis, the authors conclude 1. The form of local government responsibility is to provide access to infrastructure, access to single residential buildings inhabited by persons with disabilities, and provide facilities for pedestrians. 2. Legal consequences if the Regional Government does not carry out its responsibility to provide accessibility, that is, it will be subject to sanctions in accordance with the provisions of the applicable laws and regulations